Anion chemical composition of poly(ethylene oxide)-based sulfonylimide and sulfonate lithium ionomers controls ion aggregation and conduction. Issue 39 (14th September 2022) - Mei, Wenwen; Yu, Deyang; George, Christy; Madsen, Louis A.; Hickey, Robert J.; Colby, Ralph H.
Abstract : Higher conductivity and Li diffusion coefficient due to less aggregated morphology with sulfonylimide anion highlights the dictating role of anion chemical composition in ionomer conductivity. Abstract : Maximizing ion conduction in single-ion-conducting ionomers is essential for their application in energy-related technologies such as Li-ion batteries. Understanding the anion chemical composition impacts on ion conduction offers new perspectives to maximize ion transport, since the current approach of lowering T g has apparently reached a limit (lowest T g ∼ 190 K, highest conductivity ∼10 −5 –10 −4 S cm −1 ). Here, a series of random ionomers are synthesized by copolymerizing poly(ethylene glycol)methacrylate with either sulfonylimide lithium methacrylate (MTLi) or sulfonate lithium methacrylate (MSLi) using reversible addition–fragmentation chain transfer (RAFT) polymerization. Li-Ion conduction and self-diffusion coefficients ( D Li + ) of the ionomers are characterized with dielectric relaxation spectroscopy (DRS) and pulsed-field-gradient (PFG) NMR diffusometry, respectively. Increasing ion content decreases the Li-ion conductivity and D Li +, as expected from the increased T g . Moreover, a considerably lower ionic conductivity and D Li + are observed for MSLi compared to MTLi at constant ion content and T g / T . As revealed from X-ray scattering, strong ion aggregation in MSLi results in much lower conductivity and D Li + compared with less aggregated MTLi based on the more delocalized sulfonylimide anion. These results emphasize the detrimental and molecularly specific role of ion aggregation in Li-ion conductivity, and highlight the necessity for minimizing ion aggregation via the rational choice of anion chemical composition.